RAINBOW - Erfan Erfan; Irdhan Epria Darma Darma (FBS Universitas Negeri Padang, 2018)
Abstract The purpose of this paper is about the author's experience while enjoying the beauty of the Rainbow and in the case of plus a show in the Park of culture with the classical concept that features the works of Paganini, when it is the author's very inspired, obsessed, and greatly admired the work of it and want to make it taste the same nuanced works with wore the form composition of rondo. Impressive composition circle circular form of repetition of the song. The first theme is played, then a second theme is introduced and developed. Before the third entrance theme, the composition of the return to the first theme and finally ended back in the first theme after theme through an unexpected third. The work is played by 2player music (in the style of classical music. Consisting of Piano and violin.Keywords: Rainbow